Dysphagia in supratentorial recent small subcortical infarcts results from bilateral pyramidal tract damage. Issue 8 (October 2018) - Fandler, Simon; Gattringer, Thomas; Pinter, Daniela; Pirpamer, Lukas; Borsodi, Florian; Eppinger, Sebastian; Niederkorn, Kurt; Enzinger, Christian; Fazekas, Franz
Background: Dysphagia occurs in up to 20% of patients with a recent small subcortical infarct, even when excluding brainstem infarcts. Aim: To examine the impact of lesion topography and concomitant cerebrovascular lesions on the occurrence of dysphagia in patients with a single supratentorial recent small subcortical infarct. Methods: We retrospectively identified all inpatients with magnetic resonance imaging-confirmed supratentorial recent small subcortical infarcts over a five-year period. Dysphagia was determined by speech-language therapists. Recent small subcortical infarcts were compiled into a standard brain model and compared using lesion probability maps. Furthermore, magnetic resonance imaging scans were reviewed for the combination of both acute and old cerebrovascular lesions. Results: A total of 243 patients with a recent small subcortical infarct were identified (mean age 67.9 ± 12.2 years). Of those, 29 had mild and 18 moderate-to-severe dysphagia. Lesion probability maps suggested no recent small subcortical infarct location favoring the occurrence of moderate-to-severe dysphagia. However, patients with moderate-to-severe dysphagia more frequently showed combined damage to both pyramidal tracts by the recent small subcortical infarct and a contralateral old lesion (lacune: 77.8% vs. 19.9%, p < 0.001; lacune or confluent white matter hyperintensities: 100% vs. 57.7%, p < 0.001) than patients without swallowing dysfunction. Comparable results were obtained when analyzing patients with any degree of dysphagia. Conclusions: Preexisting contralateral vascular pyramidal tract lesions are closely related to the occurrence of moderate-to-severe dysphagia in patients with supratentorial recent small subcortical infarcts.